Glucosylceramide transferase in Giardia preferentially catalyzes the synthesis of galactosylceramide during encystation - Robles-Martinez, Leobarda (Mol Biochem Parasitol, 2016)
The stage differentiation from trophozoite to cyst (i.e., encystation) is an essential step for Giardia to survive outside its human host and spread the infection via the fecal-oral route. We have previously shown that Giardia expresses glucosylceramide transferase 1 (GlcT1) enzyme, the activity of which is elevated during encystation. We have also reported that blocking the activity of gGlcT1 interferes with the biogenesis of encystation-specific vesicles (ESVs) and cyst viability in Giardia. To further understand the role of this enzyme and how it regulates encystation, we overexpressed, knocked down, and rescued the giardial GlcT1 (gGlcT1) gene and measured its enzymatic activity in live parasites as well as in isolated membrane fractions using NBD-ceramide and UDP-glucose or UDP-galactose. We observed that gGlcT1 is able to catalyze the synthesis of both glucosylceramide (GlcCer) and galactosylceramide (GalCer), however the synthesis of GalCer is 2–3 fold higher than of GlcCer. Although both activities follow Michaelis–Menten kinetics, the bindings of UDP-glucose and UDP-galactose with the enzyme appear to be non-competitive and independent of each other. The modulation of gGlcT1 synthesis concomitantly influenced the expression cyst-wall protein (CWP) and overall encystation. We propose that gGlcT1 is a unique enzyme and that Giardia uses this enzyme to synthesize both GlcCer and GalCer to facilitate the process of encystation/cyst production.